2022
DOI: 10.1111/gcb.16108
|View full text |Cite
|
Sign up to set email alerts
|

Testing unified theories for ozone response in C4 species

Abstract: There is tremendous interspecific variability in O 3 sensitivity among C 3 species, but variation among C 4 species has been less clearly documented. It is also unclear whether stomatal conductance and leaf structure such as leaf mass per area (LMA) determine the variation in sensitivity to O 3 across species. In this study, we investigated leaf morphological, chemical, and photosynthetic responses of 22 genotypes of four C 4 bioenergy species (switchgrass, sorghum, maize, and miscanthus) to elevated O 3 in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 108 publications
1
5
0
Order By: Relevance
“…M.× giganteus genotypes also tended to have a higher A m at a given N m or P m when compared to the Glopnet species, in agreement with the observations of higher A N and A P in M.× giganteus (Table 1 1; Figure 1) (Ferguson et al, 2021). In other studies, the lowest reported A a , A m and N m values for five genotypes of sorghum were 44.3 µmol m −2 s −1 , 1426.7 nmol g −1 s −1 and 3.76% (Li et al, 2019(Li et al, , 2021 (Li et al, 2019(Li et al, , 2022. A recent study also revealed broad variation in leaf morphology across switchgrass genotypes in common garden experiments (Lovell et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…M.× giganteus genotypes also tended to have a higher A m at a given N m or P m when compared to the Glopnet species, in agreement with the observations of higher A N and A P in M.× giganteus (Table 1 1; Figure 1) (Ferguson et al, 2021). In other studies, the lowest reported A a , A m and N m values for five genotypes of sorghum were 44.3 µmol m −2 s −1 , 1426.7 nmol g −1 s −1 and 3.76% (Li et al, 2019(Li et al, , 2021 (Li et al, 2019(Li et al, , 2022. A recent study also revealed broad variation in leaf morphology across switchgrass genotypes in common garden experiments (Lovell et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…Concerning LMA, the highest value for sorghum was 35.3 g m −2 , which is much lower than the lowest values of 41.0 g m −2 in M .× giganteus . However, switchgrass ( Panicum virgatum ; three genotypes) had a similar mean LMA value with M .× giganteus (67.4 vs. 67.1 g m −2 ), but displayed overall higher mean values for A a (30.6 vs. 23.7 µmol m −2 s −1 ), A m (456.6 vs. 369.8 nmol g −1 s −1 ), and N m (3.37 vs. 2.20%) (Li et al, 2019 , 2022 ). A recent study also revealed broad variation in leaf morphology across switchgrass genotypes in common garden experiments (Lovell et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In reality, there are hundreds and thousands of plant species in each PFT and they usually have large variation in biophysical parameters including LMA and O3 sensitivities. The LMA-based approach takes advantage of the newly revealed unifying concept in O3 sensitivity (Feng et al, 2018;Li et al, 2016;Li et al, 2022) and the recent development in a trait-based LMA global map (Fig. S1a).…”
Section: Advances In the Global O3 Damage Assessmentmentioning
confidence: 99%
“…Recent observations revealed a uniform plant sensitivity to O3 if stomatal O3 flux is expressed based on leaf mass rather than leaf area (Feng et al, 2018;Li et al, 2016;Li et al, 2022). The trait of leaf mass per area (LMA) is an important metric linking leaf area to mass.…”
Section: Introductionmentioning
confidence: 99%